PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK DAPAT MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VB SDIT INSAN UTAMA PEKANBARU - Elfi Rahmi; Nelda Azriani; Hendri Marhadi; Neni Hermita (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2018)
This study is based on a low learning student’s social science outcomes. The purpose of this study is to improve the learning outcomes of IPS with the implementation of cooperative learning model type talking stick, each cycle of two meetings and a one-time test. This study was conducted on 23 subjects of primary school students’ in SDIT Insan Utama Pekanbaru. The result of this research obtained average student’s learning outcomes 76,73 with enough categories and on the second cycle student’s learning outcomes increase to 82,17 categorized well. This suggests that the cooperative model type talking stick can improve the learning outcomes of IPS on the Primary School Students.